The Five Shades of the Interplay in Horizontal Litigation Between the General Principles of EU Law on Non-discrimination and Directives - KARAYİĞİT, MUSTAFA TAYYAR (My University, 2022)
Amid the various forms of the interplay between the general principles and directives, the contribution rather deals with its five shades by focusing the main role of the directives in the legal effects of the combination of general principles and directives on horizontal litigation before the national courts in order to shed light on certain characteristics of the already very complicated Mangold line of case law, particularly arising from occasionally perplexed understanding of interaction between the general principles of EU law and directives. In that regard, it precisely examines, within the context of horizontal direct effect of the principle of non-discrimination in EU law, the role of directives in that interplay as an instrument to render the general principles of EU law applicable, to establish the existence of the general principles of EU law, to justify/exemplify the existence of the general principles of EU law, to infer from which the substantive content of the general principles of EU law and to ascertain whether the (un)conditional nature of the general principles of EU law or principles in the sense of Article 52(5) of the Charter of the Fundamental Rights of the European Union.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Hukuk; Social Sciences and Humanities; Sociology; Law; KANUN; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); LAW; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities